Income comparisons, income formation, and subjective well-being: New evidence on envy versus signaling - Heinz Welsch; Jan Kühling (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Drawing on the distinction between envy and signaling effects in income comparison, this paper uses 307,465 observations for subjective well-being and its covariates from Germany, 1990-2009, to study whether the nature of income comparison has changed in the process of economic development, and how such changes are related to changes in the nature of income formation. By conceptualizing a person's comparison income as the income predicted by an earnings equation, we find that, while in 1990-1999 envy has been the dominant concern in West Germany and signaling the dominant factor in East Germany, income comparison was non-existing in 2000-2009. We also find that the earnings equation reflects people's ability more accurately in the second than in the first period. Together, these findings suggest that comparing one's income with people of the same ability is important only when ability is insufficiently reflected in own income.
Keywords: D31; I31; J31; P36; Z13; 330; income comparison; envy; signaling; subjective well-being; income formation